Truss Morphometric Approach for population kinship analysis of Cherax quadricarinatus (Von Martens, 1868) in West Java Waters: Pendekatan Truss Morphometric Dalam Menganalisis Kekerabatan Populasi Cherax quadricarinatus (Von Martens, 1868) Di Perairan Jawa - Ali Mashar; Yuyun Sri Wahyuni; Agus Alim Hakim; Yusli Wardiatno (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2019)
Freshwater crayfish (Cherax quadricarinatus) is originate from Australia and Papua New Guinea waters. Morphometric measurement is one of the technique for differentiating body shape from a population. This study aimed to analyze the population kinship of freshwater crayfish in West Java with truss morphometric approach. Several morphometric characters were conducted measurement with a total of 133 individuals including 20 individuals from Darma Dam, 38 individuals from Kemang Lake, and 75 individuals from Kemuning Lake. The result of cluster analysis was obtained that the population of Cherax quadricarinatus from Kemuning Lake had closer relation with Kemang Lake than with Darma Reservoir. The differences in morphometric characters were alleged to be caused by differences of environmental conditions in three populations. Discriminant analysis showed that C. quadricarinatus from Darma Reservoir, Kemang Lake, and Kemuning Lake appropriately classified as 100%, 63.2%, and 76% respectively. Meanwhile, there were four main characters that differentiated the population from the three locations (C4, B5, D6, and A6).